MORPHOLOGICAL CHANGES IN CULTURED GRANULOSA CELLS FROM DIFFERENT SIZED FOLLICLES OF GOAT OVARY - SANGHA, G K; KAUR, H K; KHERA, K S (The Indian Journal of Animal Reproduction, 2023)
The granu/osa cells (GCs) from small (<2), medium (2-5) and large (>5) mm follicles of immature and mature goat ovary were aspirated and cultured in complete culture medium (McCoy’s SA medium) for studying the morphology and size related changes. GCs formed clus1ers of flattened cells with typical epitheloid morphology. The number of clusters and the GCs per cluster increased with growth of the follicle as well as with the growth of ovary. A progressive increase in diameter of granulosa cells was also observed with maturation of ovary. The cell diameter almost doubled between the small and large follicles of both immature and mature ovary.